Modelling temperature-precipitation pressures on African timber heritage - Richards, J; Brimblecombe, P; Engelstaedter, S (Wiley, 2023)
Climate parameters can be refined for use in a heritage context to capture climate-based deterioration processes occurring on buildings and sites. The Scheffer index, which combines temperature and rainfall components, is commonly used as a metric of wood decay risk. Understanding how the index is likely to change is important for developing effective conservation strategies for timber heritage. However, there has been limited research assessing the agreement between climate model outputs for such heritage-based metrics. This is especially important where capturing projected rainfall is known to be problematic, such as over regions of Africa. We address the following questions: to what extent is there model agreement over continental Africa for (i) the magnitude of the Scheffer index and (ii) the direction of change of future Scheffer indices. A multi-model ensemble (MME) approach was used utilizing 13 CMIP6 models under the SPS585 scenario. Results showed that rainfall was important in determining the magnitude of the index. In regions where rainfall systems are not well captured by climate models, such as in eastern Africa, there was a large range in projected Scheffer values. To help with the transferability of the index to regions with a tropical climate, we suggest the addition of a Scheffer threshold for a very-high risk of deterioration. Projections of future change to the index were found to be predominantly driven by changes in temperature, rather than rainfall. While there was considerable disagreement in the simulated magnitude of the Scheffer index, there was good agreement between models over the direction of change across Equatorial Africa, where the Scheffer index is greatest. Such agreement between models suggests that heritage decision makers can utilize the direction of change projected by models when shaping future conservation plans.